PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 008 RUMBIO KECAMATAN KAMPAR KABUPATEN KAMPAR - Melri Nazomi Nazomi; Jesi Alexander Alim Alexander Alim; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Background problem in this study is the low learning outcomes of the fourth grade students of SDN 008 SubdistrictKamparKampar district. with an average value of 51.16 out of 18 students who have not reached the KKM as many as 15 people (8,3%) while achieving KKM only 3 people (16,7%). The problems of this research is the application of direct learning model to improve learning outcomes Math 008 fourth grade students of SDN Rumbio District of Kampar Kampar? The purpose of this research is to improve student learning outcomes through the application of mathematics learning model directly in the class IV SDN 008 Rumbio District of Kampar Kampar district. Once applied direct instructional model, the results showed that the activity of teachers increased by 12,5% from 65% in the first cycle to 77,5% in the second cycle and then an increase of 12,5% to 90% in the third cycle. Student Activities also increased by 15% from 62,5% in the first cycle to 77,5% in the second cycle and then increased by 13% to 90,5% in the third cycle. Student Results from the baseline score increased by an average of 51,16 increased by 18,28 points to 69,44 in the next UH UH I and II value - average rose 10,28 points students from UH first to 79,72 then UH III on the average value of students increased 5 points of UH II to 84,72. Classically completeness increased from baseline 16,7% increased by 66,6% to 83,3% in the first cycle, increased again by 5,6% to 88,9% in the second cycle is further increased again by 5,5% be 94,4% in the third cycle. Based on these results it can be concluded that the hypothesis is accepted that the application of direct instructional model can improve mathematics learning outcomes 008 fourth grade students of SDN Rumbio Subdistrict KamparKampar district.